Lecanemab in a Patient with Early Alzheimer’s Disease and Cerebral Cavernous Malformation: A 12-Month Descriptive Case Report - jingwei Lyu; Yan Yun; Tong Shen; Lujie Yuan; Xin Li; Yi Li; Tan Wang (Translational Medical Engineering, 2026)
Alzheimer’s disease (AD) is a progressive neurodegenerative disorder. Anti-amyloid β (Aβ) disease-modifying therapies such as lecanemab are effective but carry risks of amyloid-related imaging abnormalities (ARIA), including intracranial hemorrhage. Safety data in patients with cerebral vascular malformations remain limited, as these populations are often excluded from pivotal trials. This article reports a 54‑year‑old female patient diagnosed with early AD combined with stable cerebral cavernous malformation (CCM). She received 24 doses of intravenous lecanemab (10 mg/kg biweekly). Over 12 months, serial MRI/SWI showed no hemorrhage, enlargement, or interval morphological change of the pontine CCM. Aβ PET-CT demonstrated a marked reduction in amyloid burden (Centiloid: 75.25 at baseline to 14 post treatment). Cognitive assessments demonstrated a mild decline during the follow-up period. An acute lacunar infarct occurred during treatment and was managed with antiplatelet therapy without hemorrhagic complications. This case enriches the clinical evidence regarding the application of lecanemab in AD patients complicated with CCM. Close, standardized neuroimaging monitoring is essential in this high-risk subgroup.